Recent nanotechnology advancements to treat multidrug-resistance pancreatic cancer: Pre-clinical and clinical overview - Alshememry, Abdullah K.; Alsaleh, Nasser B.; Alkhudair, Nora; Alzhrani, Rami; Alshamsan, Aws (Frontiers in Pharmacology, 2022)
Pancreatic cancer (PC) remains one of the most lethal and incurable forms of cancer and has a poor prognosis. One of the significant therapeutic challenges in PC is multidrug resistance (MDR), a phenomenon in which cancer cells develop resistance toward administered therapy. Development of novel therapeutic platforms that could overcome MDR in PC is crucial for improving therapeutic outcomes. Nanotechnology is emerging as a promising tool to enhance drug efficacy and minimize off-target responses via passive and/or active targeting mechanisms. Over the past decade, tremendous efforts have been made to utilize nanocarriers capable of targeting PC cells while minimizing off-target effects. In this review article, we first give an overview of PC and the major molecular mechanisms of MDR, and then we discuss recent advancements in the development of nanocarriers used to overcome PC drug resistance. In doing so, we explore the developmental stages of this research in both pre-clinical and clinical settings. Lastly, we discuss current challenges and gaps in the literature as well as potential future directions in the field.